Preparation of Gold Nanoparticles Deposited Silicon Thin Film Electrode by Self-Assembly Method for the Employment of an Anode Material for Lithium Secondary Batteries - Halim, Martin; Kim, Jung Sub; Si Hieu Nguyen; Jeon, Bup Ju; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2015)
This work describes a self-assembly method of gold nanoparticles coating on the surface of silicon thin films for the anode material of lithium secondary batteries. The preparation of the silicon thin films was carried out by electron cyclotron resonance metal organic chemical vapor deposition (ECR-MOCVD) process. The obtained films were further coated with (3-aminopropyl)-trimethoxysilane (APTMS) which has a role to bind the oxygen functional groups on Si surface and the gold nanoparticles. The dispersed gold nanoparticles on the surface of silicon thin films could be prepared due to self-assembly phenomena which interact between attraction and repulsion in gold nanoparticles colloidal solution (GNCS). The use of reducing agent of sodium citrate and tannic acid in GNCS significantly affected the size of gold nanoparticle in our experimental range. Based on our experimental results, the higher reversible capacity was exhibited for the silicon that was immersed in the GNCS consisted of only sodium citrate. The GNCS consisted of both sodium citrate and tannic acid produced severe coagulated nanoparticles when deposited on the silicon surface and thus inhibited the lithium movement from electrolyte to silicon surface. Consequently, the reversible capacity of silicon anode material with coagulated gold nanoparticles coating showed the reduced performance.
Keywords: ROOM-TEMPERATURE SYNTHESIS; SILVER NANOPARTICLES; PARTICLE-SIZE; LI; NANORODS; GROWTH